Beyond choice architecture: advancing the science of changing behaviour at scale - Theresa M. Marteau; Paul C. Fletcher; Marcus R. Munafò; Gareth J. Hollands (BMC, 2021)
Abstract Addressing the global threats to population and planetary health requires changing many behaviours at scale. This demands consideration not only of the effect size of an intervention but also its reach - the proportion of the population exposed to the intervention. We propose that a relatively under-researched and generally poorly specified set of interventions involving changes to physical micro-environments - often referred to as Choice Architecture - has the potential to make a significant contribution to meeting this urgent challenge. Realising the potential of Choice Architecture interventions requires integration of basic - i.e. laboratory-based - and applied - i.e. field-based - research, generating interventions that can be delivered at scale alongside advancing theory. We illustrate this with examples to highlight the complementarity of laboratory and field studies informed by and in turn updating the results of evidence synthesis. The examples comprise two sets of interventions - changing the relative availability of products and changing their size - to reduce consumption of meat, energy from food and alcohol across populations.